Does Being "Left–Behind" in Childhood Lead To Criminality in Adulthood? Evidence from Data on Rural-Urban Migrants and Prison Inmates in China - Lisa A. Cameron; Xin Meng; Dandan Zhang (Institute of Labor Economics (IZA), 2021)
Large scale rural-to-urban migration and China's household registration system have resulted in about 61 million children being left-behind in rural villages when their parents migrate to the cities. This paper uses survey and experimental data from male rural-urban migrants – prison inmates and comparable non-inmates – to examine whether parental absence in childhood as a result of migration is associated with increased criminality in adulthood. Control functions and sibling fixed effects are used to identify causal impacts. Parental absence due to migration is found to increase the propensity of adult males to commit crimes. Being left-behind decreases educational attainment and increases risk-loving behavior, both of which increase criminality.
Keywords: O12; O15; J12; 330; migration; crime; China